Callorhinus ursinus - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Callorhinus ursinus (Linnaeus 1758) [Phoca] ursina Linnaeus 1758, Syst. Nat., 10th ed., Vol. 1: 37. Type Locality: "in Camschatcæ maritimus inter Asiam and Americam proximam, primario in infula Beringri," restricted by Thomas (1911 a ) to "Bering Island.". Vernacular Names: Northern Fur Seal. Synonyms: Callorhinus alascanus (Jordan and Clark 1898); Callorhinus californianus (Gray 1866); Callorhinus curilensis (Jordan and Clark 1899); Callorhinus cynocephala (Walbaum 1792); Callorhinus krachenninikowii (Lesson 1828); Callorhinus mimica (Tilesius 1835); Callorhinus nigra (Pallas 1811). Distribution: North Pacific coastal regions in Canada, China (vagrant to Shandong), Japan, Mexico (costs of Baja California), Russia (Okhotsk and Bering Seas, Commander and Pribilof Isls), USA (Alaska, Washington, Oregon, S California). Conservation: IUCN – Vulnerable. Discussion: Subspecies not recognized, following Taylor et al. (1955) and Rice (1998). Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Carnivora, pp. 532-628 in Mammal Species of the World: a Taxonomic and Geographic Reference (3 rd Edition), Volume 1, Baltimore :The Johns Hopkins University Press on page 592, DOI: 10.5281/zenodo.7316519